Pembuatan Aplikasi untuk Pengaturan Jasa Service Sepeda Motor Pada Toko X - Handojo, Steven Halim; Noertjahyana, Agustinus; Purbowo, Anita Nathania (Jurnal Infra, 2018)
Information technology continues to grow along with the times. Technological advances also make the standard of service to customers to be different. Shop X is a business in the field of motor service services. Currently ordering service is still done by manual. This makes the initial service collection becomes longer because it is only done by one person, so it is necessary to change the ordering method to be online.Making motorcycle booking service applications aims to assist customers in ordering service vehicles without having to come to the garage. The application for the customer is made with android platform and uses java programming language, while the application for the admin is made with the website platform and using HTML, PHP, MySQL, and Bootstrap programming languages.The result of making the application is the user can make vehicle booking service via Android without having to come to the workshop, the user can receive notification of vehicle re-service, and admin application can determine vehicle booking service quotas